Studying the potential of slag waste particle as suspended solid drag reducing agent - Siti Nuraffini, Kamarulizam; Abdulbari, Hayder A.; Arumugam, Nithiya (IEEE, 2011)
Main by product in ore smelting which is slag from tin production in Malaysia has become a trigger for this investigation. Slag waste can be categorized as suspended solid. Utilization of this waste in transportation of fluid can reduce the pressure drop in pipelines. Several studies have shown that addition of minute quantities of suspended solid additives can reduce the drag in pipe and maintain the pressure drop along the pipelines. Experimental works have been conducted in the laboratory in order to test slag waste in a closed loop of turbulence water flowing system. Flow tests were conducted using water as the transport liquid. The experimental work starts by pumping water from reservoir tank that had mixed with slag powder was pumped with varies flow rates in two different pipe diameters (0.025 m ID and 0.038 m D.I). The types of pipe used are PVC pipe. The testing length of this flow system is 2.0 m. The pressure drop and drag reduction were measured in the flow varying concentrations of suspended solid (slag). After adding the suspended solid to the water, the results have shown that the percentage drag reduction (Dr%) over 60% in certain range and condition. This experiment has proven that slag waste particle can be a potential drag reducer in flow system.